Sex, Condoms and Sexually Transmissible Infections: A Qualitative Study of Sexual Health in Young Australian Men - Smith, Jennifer; Fenwick, Jennifer; Skinner, R.; Hallett, Jonathan; Merriman, Gareth; Lewis, M. (SprinkerLink, 2012)
Young males have a key role in shaping contraceptive use in a sexual relationship, yet often remain the invisible partner in safe sex promotion. This article describes a conceptual model of STI risk and condom use based on the perceptions and experiences of condom use in a group of young Australian males. An explorative descriptive design was used to conceptualize participants’ condom use histories into an organized description of behavior. Forty-two semi-structured interviews were conducted with a purposive sample of males aged 15 to 25 years over an 18 month period. A sequential analytical process of data immersion, coding, and category generation was used to identify personal meanings, motivations, and contextual factors associated with condom use and non-use. Three primary discourses associated with young males’ perceptions of STI risk and responding approach to condom use constructed personal commitment to sexual safety as dynamic, context-dependent, and outcome-driven (pregnancy versus STIs as the primary motivator of condom use). A regretful discourse associated with experiences of, or suspected unwanted outcomes, also emerged through changes in risk appraisals and safe sex intentions and behavior. Interventions to increase condom use should go beyond the traditional focus on risky behavior and disease prevention frameworks by addressing the contextual influences on personal risk appraisals and deliver innovative messages to reduce negative social meanings associated with condom use.